Bacterial Wilt in China: History, Current Status, and Future Perspectives - Jiang, Gaofei; Wei, Zhong; Xu, Jin; Chen, Huilan; Zhang, Yong; She, Xiaoman; Macho, Alberto P.; Ding, Wei; Liao, Boshou (Frontiers in Plant Science, 2017)
Bacterial wilt caused by plant pathogenic Ralstonia spp. is one of the most important diseases affecting the production of many important crops worldwide. In China, a large scientific community has been dedicated to studying bacterial wilt and its causative agent, R. pseudosolanacearum and R. solanacearum. Most of their work was published in Chinese, which has hindered international communication and collaboration in this field. In this review, we summarize the status of knowledge on geographical distribution, diversity, and host range of Ralstonia spp., as well as, the impact of bacterial wilt on important crops and disease control approaches, in China. We present areas of research and publications by Chinese scientists and propose the promotion of collaborative research within China and with the international community.